SIMBOLIKHAJI: Studi Deskriptif Analitik pada Orang Bugis - Andi Agustang (Al-Qalam, 2009)
As stated by Berger, Hajj as religious practice is attached to culturalcontext and meaning dialecticism. The difference of hajj symbol as culturalproduct construction from others laid on its transcendence and itsreligious dimension. Its cultural meaning has also changed overtime.This change can be looked on the newly hajj interpretation which hasdeviated from its true meaning written in Islamic texts, and implicatedto the current Buginese community social and cultural practice andinter relation. As the symbol of hajj relatively attached more to the femalehajj, the number of female hajj, as its implication, is more higherthan male hajj.